Enforcement of the duties of directors by the securities and futures investors protection center in Taiwan - CHEN, Christopher C. H. (Institutional Knowledge at Singapore Management University, 2014)
The purpose of this article is to examine the role of the Securities and Futures Investors Protection Center (SFIPC) in Taiwan in enforcing the duties of directors. To help shareholders or investors pursue a director for breach of company law or securities regulations, Taiwan created the SFIPC, a charity sanctioned by statutes, to bring class action or direct legal action on behalf of minority shareholders or individual investors. By conducting an empirical survey of judgments from lawsuits involving the SFIPC since its creation, we found that the SFIPC is generally very active in enforcing securities regulations but far less active in breaches of company law. This reflects the public nature of the institution as well as a fundamental defect regarding directors’ fiduciary duties and statutory derivative action in Taiwan’s company law. The SFIPC has shown strong performance in the civil courts but has a dismal record in the criminal courts. If the past is a guide, then regulators in Taiwan should reconsider the role of the SFIPC if its goal is to strengthen the enforcement of corporate director liability and address the shortcomings of derivative actions in company law.